Rapid Identification of Relevant Microbial Strains by Identifying Multiple Marker Single Nucleotide Polymorphisms via Amplicon Sequencing: Epidemic Monkeypox Virus as a Proof of Concept - Sergio Buenestado-Serrano; Marta Herranz; Rosalía Palomino-Cabrera; Cristina Rodríguez-Grande; Daniel Peñas-Utrilla; Andrea Molero-Salinas; Cristina Veintimilla; Pilar Catalán; Roberto Alonso; Patricia Muñoz; Laura Pérez-Lago; Darío García de Viedma (Microbiology Spectrum, 2023)
ABSTRACT Despite the proven value of applying genomic data for epidemiological purposes, commonly used high-throughput sequencing formats are not adapted to the response times required to intervene and finally control outbreaks. In this study, we propose a fast alternative to whole-genome sequencing (WGS) to track relevant microbiological strains: nanopore sequencing of multiple amplicons including strain marker single nucleotide polymorphisms (SNPs). As a proof a concept, we evaluated the performance of our approach to offer a rapid response to the most recent public health global alarm, the monkeypox virus (MPXV) global outbreak. Through a multisequence alignment, a list of 42 SNPs were extracted as signature makers for this outbreak. Twenty primer pairs were designed to amplify in a multiplex PCR the regions including 22 of these SNPs. Amplicon pools were sequenced in a MinION device, and SNPs were called in real time by an in-house bioinformatic pipeline. A total of 120 specimens (95 MPXV-PCR positive, Ct values from 14 to 39) were selected. In 67.37% of the positive subset, all 22 SNPs were called. After excluding low viral load specimens, in 92% of samples ≥11 outbreak SNPs were called. No false positives were observed in any of the 25 negative specimens. The total turnaround time required for this strategy was 5 hours, and the cost per sample was 14 euros. Nanopore sequencing of multiple amplicons harboring signature SNPs escapes the targeting limitations of strain-specific PCRs and offers a powerful alternative to systematic WGS, paving the way to real-time genomic epidemiology and making immediate intervention possible to finally optimize transmission control. IMPORTANCE Nanopore sequencing of multiple amplicons harboring signature single nucleotide polymorphisms (SNPs) escapes the targeting limitations of strain-specific PCRs and offers a powerful alternative to systematic whole-genome analysis, paving the way to real-time genomic epidemiology and making immediate intervention possible to finally optimize transmission control.